2023
DOI: 10.3390/molecules28073217
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Molecular Rotors Based on Hinged Anthracene Carboxyimides

Abstract: Temperature and viscosity are essential parameters in medicine, environmental science, smart materials, and biology. However, few fluorescent sensor publications mention the direct relationship between temperature and viscosity. Three anthracene carboxyimide-based fluorescent molecular rotors, 1DiAC∙Cl, 2DiAC∙Cl, and 9DiAC∙Cl, were designed and synthesized. Their photophysical properties were studied in various solvents, such as N, N-dimethylacetamide, N, N-dimethylformamide, 1-propanol, ethanol, dimethyl sulf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…To solve these issues, it was found that the nonradiative decay of the excited state of the fluorescent molecular rotors can be changed by the environmental viscosity, which has become a new method to determine the microviscosity changes in a biological environment. 22,23 Additionally, fluorescence imaging was wellknown for high spatiotemporal resolution, invasiveness, and sensitivity. 24−26 Especially, the near-infrared (NIR) region (>650 nm) fluorescent dyes with large Stokes shifts have better penetration depth and antibackground interference ability and therefore are widely applied in biomedical analysis and diagnosis caused by changes in the microenvironment.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To solve these issues, it was found that the nonradiative decay of the excited state of the fluorescent molecular rotors can be changed by the environmental viscosity, which has become a new method to determine the microviscosity changes in a biological environment. 22,23 Additionally, fluorescence imaging was wellknown for high spatiotemporal resolution, invasiveness, and sensitivity. 24−26 Especially, the near-infrared (NIR) region (>650 nm) fluorescent dyes with large Stokes shifts have better penetration depth and antibackground interference ability and therefore are widely applied in biomedical analysis and diagnosis caused by changes in the microenvironment.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Because of the limitations of detection methods, there are few studies on viscosity as an important marker of microenvironments in biological processes and disease diagnosis. To solve these issues, it was found that the nonradiative decay of the excited state of the fluorescent molecular rotors can be changed by the environmental viscosity, which has become a new method to determine the microviscosity changes in a biological environment. , Additionally, fluorescence imaging was well-known for high spatiotemporal resolution, invasiveness, and sensitivity. Especially, the near-infrared (NIR) region (>650 nm) fluorescent dyes with large Stokes shifts have better penetration depth and antibackground interference ability and therefore are widely applied in biomedical analysis and diagnosis caused by changes in the microenvironment. Up to now, the rotors and fluorophores of most viscosity-responsive probes were connected with double bonds or single bonds . In a low-viscosity environment, the probe releases weak fluorescence resulting from the free rotation of rotor-connected single or double bonds, while as viscosity increases their rotation was inhibited by forming a large conjugated system, and result in strong fluorescence in a tall-viscosity environment. , Interestingly, most rhodamine and other fluorophores-based viscosity probes, their rotors are composed of aromatic ring: benzo-indole, polyaniline group, benzo-thiophene, pyridine salt, quinoline, imidazole, azobenzene, etc.…”
Section: Introductionmentioning
confidence: 99%